2020
DOI: 10.30574/wjarr.2020.5.1.0112
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and abundance of macrophytes of streams under different anthropogenic influences in the Buea municipality, southwestern Cameroon

Abstract: Macrophytes can occur as submerged, floating or emergent. They provide not only important structural supports in streams and river habitats, but also absorb and sequester pollutants, provide primary food production, nutrients and habitats to a wide range of macro and micro-organisms living in and around lotic sites. Their existence is however threatened by both anthropogenic and natural stresses. This study aimed to document macrophyte diversity and abundance in streams under different anthropogenic influences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Other activities in the stream include bathing, laundry and subsistent fishing. Studies on the diversity and abundance of macrophytes in the stream revealed a total of 48 species, in 40 genera and 24 families, made up of submerged and emergent categories [32].…”
Section: Description Of Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Other activities in the stream include bathing, laundry and subsistent fishing. Studies on the diversity and abundance of macrophytes in the stream revealed a total of 48 species, in 40 genera and 24 families, made up of submerged and emergent categories [32].…”
Section: Description Of Study Sitementioning
confidence: 99%
“…Macrophyte assessment was done using a 500 m long transect whose width was the entire span of the wetland including the stream itself [32]. The transect was laid out to cover points before and after the carwash points so as to capture the impact of point source pollution from the activity and also non-point source pollution on the stream and its biota.…”
Section: Plant Samplingmentioning
confidence: 99%